Socio-Demographic Determinants of Poverty in Nigeria and its Gender Differentials - Buba, Abdullahi; Abdu, Musa; Adamu, Idi; Jibir, Adamu (European Scientific Journal, ESJ, 2018)
Poverty reduction is one of the greatest challenges facing international community and it is an invaluable requirement for sustainable development. This study was conducted to empirically examine the influence of socioeconomic as well as demographic variables on households’ vulnerability to social exclusion or deprivation with more emphasis on gender inequality. The study employed binary probit regression analysis of poverty as well as Oaxaca-Blinder decomposition to examine factors responsible for inequality with respect to socio-economic fortunes among Nigerian households. Evidence from the study revealed that socio-demographic variables as well as labor characteristics are strong determinants of poverty in the country, and the findings confirmed to the theoretical propositions on causes of poverty. However, empirical results from the Oaxaca-Blinder decomposition show that female headed households are more disadvantaged in terms of socioeconomic deprivation than the male headed households. The study concluded by presenting concluding remarks and policy implications for policymakers toward poverty reduction in Nigeria.